The response of long-term interest rates to news about monetary policy actions: Empirical evidence for the US and Germany - Dieter Nautz; Jürgen Wolters (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1998)
We reexamine the expectations theory of the term structure focusing on the question how monetary policy actions indicated by changes in the very short rate affect long-term interest rates. Our main point is that the expectations hypothesis implies that very long rates should only react to unanticipated changes of the very short rate. In contrast to cointegration tests of expectations theory this implication only requires rational expectations but not stationary risk premia. Therefore, its empirical test sheds new light on the importance of expectations theory for the determinants of the term structure of interest rates.
urn:nbn:de:kobv:11-10060557
Keywords: 330